Relationship of Quantitative Traits in Different Morphological Characters of Pea (Pisum Sativum L.) - Sarah Tasnim; Nilufa Yasmin Poly; Nusrat Jahan; Ahasan Ullah Khan (Pandawa Institute, 2022)
An experiment was undertaken to elucidate the genetic relationship between different quantitative traits for commercial cultivation and to evaluate selection criteria in pea breeding programs in five inbred parents. Their 17 F4’s derivatives in pea (Pisum sativum L.) evaluated ten characters during the winter season (November to February) of 2017-18 at the research farm, BSMRAU, Gazipur, Bangladesh. Analysis of variance explored significant differences among the genotypes for all the characters. Phenotypic coefficients of variation (PCV) were close to genotypic coefficients of variation (GCV) for all the characters indicating less influence on the environment and potentiality of selection. A high heritability relationship with high genetic advance was observed for plant height, pod per plant, hundred seed weight, and seed yield per plot. Pod length showed a highly significant positive correlation with pod width and hundred seeds weight. Only days to first flowering showed a highly negative correlation with pod length and hundred seed weight. Path coefficient analysis revealed that plant height, pod per plant, and seeds per pod had a highly positive effect on yield per plant. Therefore, associating and selecting those traits, yield improvement must be possible in pea, and the days to maturity, plant height, pods per plant, pod length, and seed showed a considerable positive and highly significant correlation with plant height, pod per plant, seed per pod, and yield per plant at both genotypic and phenotypic levels indicating yield could be increased with the increase of days to maturity, plant height, pods per plant, pod length, and seed.